2014
DOI: 10.1002/cvde.201407123
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of TiOx/Al2O3 Bilayer Structures for Resistive Switching Memory Applications

Abstract: The resistive switching (RS) properties of a thin Al2O3 layer and TiOx/Al2O3 bilayers integrated into TiN/metal oxide/Pt crossbar devices are investigated for future memristive device (ReRAM) applications. The oxide bilayer stack is realized in consecutive atomic layer deposition (ALD) processes at 300 °C without any post‐annealing step. Stoichiometric Al2O3 and oxygen‐deficient TiOx thin films are grown from dimethylaluminum isopropoxide [DMAI: (CH3)2AlOCH(CH3)2] and tetrakis‐dimethlyamido‐titanium [TDMAT: Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…These cells show indeed a highly resistive HRS, a high forming voltage and an abrupt reset characteristic [22]. Consistent results for hybrid resistive switching layers have also been demonstrated in [23]. Zhang It is then conceivable that the is switching as well as the layer.…”
Section: A Resistance Ratio Improvementsupporting
confidence: 67%
“…These cells show indeed a highly resistive HRS, a high forming voltage and an abrupt reset characteristic [22]. Consistent results for hybrid resistive switching layers have also been demonstrated in [23]. Zhang It is then conceivable that the is switching as well as the layer.…”
Section: A Resistance Ratio Improvementsupporting
confidence: 67%
“…If the switching in these heterostructures was dominated by the inserted retention-stabilization layer, however, we would expect a different shape or even the opposite switching direction, as was demonstrated before for resistive switching in Al 2 O 3 (ref. 55 ). Instead, we observed that the shape and polarity of the I – V characteristics as well as the absolute voltages and currents, which are typically observed in these heterostructures, were still the same as for SrTiO 3 thin-film devices ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By purely empirical studies and without paying special attention to oxygen transport properties of the materials under consideration, several groups already observed improved device performance in memristive devices with inserted Al 2 O 3 layers, such as improved uniformity of HfO x - and TaO x -based devices 59 60 , improved memory windows in TiO x -based devices 55 and improved retention in GdO x -based devices 61 . On the basis of these observations, it can be assumed that our concept of the rationally designed retention-stabilization layer can be extrapolated from our model system to technologically more relevant systems.…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of applying multiple coating steps also opens the way to sol-gel processed double-layer structures [69], which brings potential benefits that span from increased endurance to reduced power consumption [44,[70][71][72]. For instance, in TiO 2 -based memristors oxygen vacancies migration can lead to oxygen gas evolution at the anode, which irreversibly compromises the oxide stoichiometry: the presence of a blocking layer can act as sink of oxygen ions and limit currents involved, avoiding oxide breakdown [3,73,74].…”
Section: Dependence Of Switching Behavior On Metal Oxide Characteristicsmentioning
confidence: 99%